Presenting features and molecular genetics of primary hyperparathyroidism in the paediatric population. Issue 2 (February 2021) - El Allali, Yasmine; Hermetet, Coralie; Bacchetta, Justine; Amouroux, Cyril; Rothenbuhler, Anya; Porquet-Bordes, Valérie; Champigny, Marie-Alexandrine; Baron, Sabine; Barat, Pascal; Bony-Trifunovic, Hélène; Bourdet, Karine; Busiah, Kanetee; et al.
Abstract : Aim: To describe the presenting features and molecular genetics of primary hyperparathyroidism (PHPT) in the paediatric population. Methods: Retrospective study of 63 children diagnosed with primary PHPT from 1998 to 2018. Results: Compared to older children, infants were often asymptomatic (54% vs 15%, P  = 0.002) with a milder form of PHPT. When symptomatic, children and adolescents mostly presented with non-specific complaints such as asthenia, depression, weight loss, vomiting or abdominal pain. A genetic cause of PHPT was identified in about half of this cohort (52%). The infancy period was almost exclusively associated with mutation in genes involved in the calcium-sensing receptor (CaSR) signalling pathway (i.e. CaSR and AP2S1 genes, 'CaSR group'; 94% of infants with mutations) whereas childhood and adolescence were associated with mutation in genes involved in parathyroid cell proliferation (i.e. MEN1, CDC73, CDKN1B and RET genes, 'cell proliferation group'; 69% of children and adolescents with mutations). Although serum calcium levels did not differ between the two groups ( P  = 0.785), serum PTH levels and the urinary calcium/creatinine ratio were significantly higher in 'cell proliferation group' patients compared to those in the 'CaSR group' ( P  = 0.001 and 0.028, respectively). Conclusion: Although far less common than in adults, PHPT can develop in children and is associated with significant morbidity. Consequently, this diagnosis should be considered in children with non-specific complaints and lead to monitoring of mineral homeostasis parameters. A genetic cause of PHPT can be identified in about half of these patients.